Handbook of Islamic banking - Hassan, Kabir; Lewis, Mervyn (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2007)
The book comprises 25 studies by leading international experts on islamic banking and finance specifically commissioned to analyse the various debates and the current state of play in the field.
Includes bibliographical references and index.
nif 25/04/13
Loans
Keywords: Banks and banking; Banks and banking